A Randomized Clinical Trial Comparing Itraconazole and a Combination Therapy with Itraconazole and Potassium Iodide for the Treatment of Feline Sporotrichosis - Erica Guerino dos Reis; Sandro Antonio Pereira; Luisa Helena Monteiro de Miranda; Raquel de Vasconcellos Carvalhaes de Oliveira; Marcel de Souza Borges Quintana; Paula Gonçalves Viana; Anna Barreto Fernandes Figueiredo; Cindy Caroline dos Santos Honorato; Gabriela Reis Pereira-Oliveira; Jéssica Nunes Silva; Tânia Maria Pacheco Schubach; Isabella Dib Ferreira Gremião (Journal of Fungi, 2024)
Feline sporotrichosis is an endemic disease with high occurrence in Brazil. Itraconazole (ITZ) remains the drug of choice for treating this disease in cats, despite the increasing reports of therapeutic failure. A controlled, randomized clinical trial was performed on 166 naive cats with sporotrichosis to assess the effectiveness and safety of the combination therapy with ITZ and potassium iodide (KI) compared with ITZ monotherapy. Cats were randomly allocated into two treatment groups: G1—ITZ 100 mg/cat/day—and G2—ITZ 100 mg/cat/day + KI 2.5–20 mg/kg/day. Cats treated in G2 presented 77% more risk of reaching a clinical cure (a positive effect) than those treated in G1, even when controlled by negative predictors. The survival curves of the two treatment protocols indicate that a clinical cure was achieved faster in G2. An increase in the KI dose was necessary in 28 cats due to the persistence of clinical signs. Adverse reactions were equally frequent in both groups and manageable with a temporary drug suspension and/or a hepatoprotective therapy. The combination therapy was associated with a higher cure rate and a shorter treatment time, suggesting that ITZ+KI arises as a better option for treating feline sporotrichosis and should be considered the first-line treatment, especially in the presence of negative predictors.